2020
DOI: 10.1111/cen.14293
|View full text |Cite
|
Sign up to set email alerts
|

Less ready for adulthood?—Turner syndrome has an impact on transition readiness

Abstract: Objective Young women with Turner syndrome (TS) are known to be at risk for loss to medical follow‐up. Recent literature indicates that there are disparities regarding transition readiness between different chronic conditions. So far, studies in young women with TS investigating their transition readiness compared to youths with other chronic conditions with no or minor neurocognitive challenges have not been reported. Methods Patients (n = 52), 26 patients with Turner syndrome (mean age 17.24 ± 2.10) and 26 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Though the problem is underestimated around the world, with some exceptions, implementing and refining protective measures aimed at reducing the loss of follow-up and related consequences in terms of morbidity and mortality is a burden that cannot be ignored any longer. With a synchronised and multidisciplinary endeavour, ultimately, subjects suffering from CHD should be able to achieve the goal of a smooth transition to adult-oriented follow-up ( Figure 3 ) [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though the problem is underestimated around the world, with some exceptions, implementing and refining protective measures aimed at reducing the loss of follow-up and related consequences in terms of morbidity and mortality is a burden that cannot be ignored any longer. With a synchronised and multidisciplinary endeavour, ultimately, subjects suffering from CHD should be able to achieve the goal of a smooth transition to adult-oriented follow-up ( Figure 3 ) [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has been used in endocrinology to compare young people with Turner syndrome to those with type 1 diabetes, and revealed that those with Turner syndrome are less mature in the management of their healthcare and may find the process of transfer to adult services difficult. 51 This aspect is, however, also connected with national healthcare policies. Mobile devices, such as smartphone apps (e.g.…”
Section: Unmet Needs In Growth Disorder Management: Digital Solutionsmentioning
confidence: 99%
“…Guidelines and recommendations to facilitate the transition of AYAs with Turner syndrome have been updated in the last 2-3 years [31,33,34,38], but studies suggest that women with Turner syndrome continue to be unprepared for transition [39,40]. Low confidence regarding independence in self-management is one reported factor [41 & ].…”
Section: Turner Syndromementioning
confidence: 99%